1987
DOI: 10.1021/bi00392a015
|View full text |Cite
|
Sign up to set email alerts
|

Active site of human liver aldehyde dehydrogenase

Abstract: Bromoacetophenone (2-bromo-1-phenylethanone) functions as an affinity reagent for human aldehyde dehydrogenase (EC 1.2.1.3) and has been found specifically to label a unique tryptic peptide in the enzyme. Amino-terminal sequence analysis of the labeled peptide after purification by two different procedures revealed the following sequence: Val-Thr-Leu-Glu-Leu-Gly-Gly-Lys. Radioactivity was found to be associated with the glutamate residue, which was identified as Glu-268 by reference to the known amino acid seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
57
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 22 publications
1
57
0
Order By: Relevance
“…3) shows that the residues Glu 270 , Cys 304 , and Gln 489 , which are thought to be involved in the catalytic role of ALDH enzymes (41)(42)(43), were highly conserved in Xenopus sequences. The region participating in T 3 binding by xCTBP/xALDH1 is located at amino acid positions 92-107.…”
Section: Discussionmentioning
confidence: 99%
“…3) shows that the residues Glu 270 , Cys 304 , and Gln 489 , which are thought to be involved in the catalytic role of ALDH enzymes (41)(42)(43), were highly conserved in Xenopus sequences. The region participating in T 3 binding by xCTBP/xALDH1 is located at amino acid positions 92-107.…”
Section: Discussionmentioning
confidence: 99%
“…By performing site-directed mutagenesis with the rat liver enzyme, we now find that the residue is cysteine 302 (63), as originally suggested by Hempel and Pietruszko (25). Recently, however, it was found that in sheep liver cytosolic ALDH, serine 74 could be modified by a substrate (38 It was reported that glutamate 268 in the human cytosolic enzyme appeared to be essential for activity (1,2). This is also a highly conserved residue in all species.…”
Section: Discussionmentioning
confidence: 99%
“…These residues were conserved in all other mitochondrial and cytosolic enzymes, although for the bovine enzyme the sequence was not yet extended beyond residue 72. Cys-302, a disulfiram-reactive residue in human aldehyde dehydrogenase [51], has been implicated in NAD binding [52] and is also found in all aldehyde dehydrogenases, as is Glu-268, which has been postulated to be catalytically essential [53]. Finally, Glu-487, a substituted residue in the inactive isozyme isolated from many oriental individuals [33], is conserved in all species.…”
Section: Discussionmentioning
confidence: 99%